LITERASI DESA PENDAWAN SEBAGAI DESA WISATA - Wulan Purnamasari; U. Sulia Sukmawati; Oskar Hutagaluh (Jurnal Pengabdian Kepada Masyarakat, 2022)
Pendawan Village has a large market area and there is also a terminal, seeing its strategic location so there is a desire to change the nickname from Slum Village to Tourism Village. For this reason, the activities of the Community Service (PKM) of the Sultan Muhammad Syafiuddin Sambas Islamic Institute in collaboration with the Department of Tourism, Youth and Sports (DISPORA) of Sambas Regency aim to support the development of Pendawan Village as a Tourism Village, the potential and obstacles of Pendawan Village to become a tourist village. In the implementation of PKM, using the PRA (Participatory Rural Appraisal) approach supported by interview and observation methods in data collection. The result of this activity is that the Village knows the steps to become a Tourism Village, one of which is forming a Tourism Awareness Group (PokDarWis).